Friction model of fingertip sliding over wavy surface for friction-variable tactile feedback panel. (17th October 2016) - Fujii, Yohei; Okamoto, Shogo; Yamada, Yoji
Graphical Abstract: Abstract : A friction-variable touch panel is capable of presenting virtual bumps and holes on its flat surface through the control of the surface friction when a fingertip slides over it. To improve the presentation, we developed a friction model of a fingertip sliding over a sinusoidal surface with an amplitude of 0.5–2.5 mm and a spatial wavelength of 20–50 mm. When a metal ball rolls over a wavy surface with a low friction and contact area, the ratio of the horizontal force to the normal force is equal to the gradient of the surface (this is referred to as the ball bearing model) and is hardly affected by the normal load and rolling speed. In contrast, the profile of the force ratio of a sliding finger is substantially skewed and affected by the sliding direction and normal force exerted by the finger. To model this skewed force ratio, we formulated the asymmetric pressure distribution in the finger-surface contact area and used the effects of the adhesion friction to model the dependency of the force ratio on the normal force and sliding direction. The developed model of a bare finger with these features was found to sufficiently simulate the experimentally observed force ratios. The model can be easily applied to friction-variable touch panels and enables the achievement of a wide variety of haptic contents with macroscopically concave or convex surfaces.